The occurrence and extent of collapse settlement in residual granite in the Stellenbosch area - Gildenhuys, Nanine (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Civil Engineering))--University of Stellenbosch, 2010.